Mind, machine and morality : toward a philosophy of human-technology symbiosis - Hancock, Peter A., 1953- (Farnham, England ; Burlington, VT : Ashgate, 2009)
1. The science and philosophy of human-machine systems ##- 2. Teleology for technology ##- 3. Convergent technological evolution ##- 4. The future of function allocation ##- 5. The sheepdog and the Japanese garden ##- 6. On the future of work ##- 7. Men without machines ##- 8. Life, liberty, and the design of happiness ##- 9. Mind, machine and morality.
Includes bibliographical references (p. [161]-177) and index.
boek